Selection of F6 soybean lines for Chapadão do Sul (Research, Society and Development, 2020)
Soybean is a crop of great economic importance for Brazil, being the main crop of Brazilian agribusiness. For this reason, soybean is exploited in genetic breeding programs, which aim to make available cultivars with high grain yield and adaptability to the different farming regions. The objective of this work was to select F6 soybean lines with high yield, besides favorable traits for the municipality of Chapadão do Sul, in Brazilian Cerrado. The experiments were carried out in the experimental area of the Federal University of Mato Grosso do Sul, Campus of Chapadão do Sul-MS, in the 2017/2018 and 2018/2019 harvests. Forty-eight F6 lines and six commercial cultivars were evaluated in augmented block design, with six replicates for each control. In the first experiment (2017/2018 harvest), the following variables were evaluated: number of days for maturity (cycle), and grain yield (PROD, kg ha-1). In the second experiment (2018/2019 harvest), the variables evaluated were: main stem diameter (DHP, cm), mass of hundred grains (MCG, g), and PROD. The coefficients of variation were less than 10%, indicating higher homogeneity between the data and low random variation. The index ( ) used here has provided agronomic gains in the desired direction for most traits, except DHP. The lines: L4, L16, L18, L23, L25, L30, L31, L32, L40 and L47 stand out as superior genotypes in the selection, with respect to yield in the two years, MCG, and cycle shortening.